Employee Engagement Memediasi Pengaruh Work Life Balance dan Kepuasan Kerja Terhadap Intention to Leave - Siwi Dyah Ratnasari; Muchammad Rifqi Widitama; Sunarto (Fakultas Ekonomi Universitas Kadiri, 2023)
The first goal of this study is to ascertain how work-life balance affects employee engagement. 2) ascertain how work satisfaction affects employee engagement. 3) assess how work-life balance affects the intention to leave. 4) ascertain how to work happiness affects the intention to depart. 5) ascertain how employee engagement affects the intention to leave. A descriptive study with a quantitative methodology is the research style adopted. The 140 staff members of Lawang Medika Hospital comprise the entire research population. The Slovin method created the sample for this investigation, which yielded 104 participants. The stratified proportional random sampling method was used to choose the sample size. The proportional principle of the number of employees per division is used in this selection method. Primary data is the source of research information. Employees at Lawang Medika Hospital Malang were the respondents, and questionnaires were distributed as the data collection technique. The findings revealed that: 1) Work-life balance significantly improved employee engagement. 2) Employee engagement is significantly positively impacted by job satisfaction. 3. The intention to leave is significantly impacted negatively by work-life balance. 4) The intention to leave is very negatively impacted by job satisfaction. 5) The intention to leave is significantly impacted negatively by employee engagement. The study's findings suggest that employers should keep giving staff members a balance of time for their job and personal lives. Giving job grades encourages the timely completion of tasks.